Editorial: Family in the 19th and 20th Centuries - Topij-Stempińska, Beata (Horyzonty Wychowania, 2020)
The 19th century was the period characterised by frequent and rapid transformations affecting material, economic, cultural, and political aspects of the social life in which only the family seemed to have maintained its significant role, remaining a specifically unchangeable and permanent social group...